Religious Education and Sacred Study in the Teachings of Rabbi Yitshak Hutner - Mayse, Ariel Evan (Religions, 2019)
Rabbi Yitshak Hutner (1906-1980) was a remarkable scholar, an enigmatic religious intellectual and a charismatic teacher. Drawing upon his public discourses and his written letters, I argue that Hutner's vocabulary-which remained rooted almost entirely in the vocabulary of traditional Talmudism-afforded him a ready garment in which to clothe a syncretic educational theory, which combines Hasidic approaches to spiritual instruction and remakes the traditions of Lithuanian piety and study for his new American audience. The present study interrogates a series of key themes that appear in Hutner's teachings, all of which pertain to issues of pedagogy and the construction of religious education. The essay advances a historical argument by examining the works of an important and influential modern Jewish thinker, but it is also driven by a constructive question: What does Hutner's vision of Jewish religious teaching and learning have to contribute to today's Jewish education, and to the broader world of higher education in North America in particular?